The Use of Comic Strips to Tech Reading Narrative Text to the Ninth Grade Students of MTs. Al Abror - Putri Ika samsulia (PGRI Provinsi Jawa Timur, 2021)
The students are hoped for understand the narrative text, but many students still find the difficulties in reaching the goal. Students face several problems when they read narrative text. Mostly, the students find the difficulty in orientation the text. This research aims to teach reading the ninth grade students’ narrative text in MTs Al Abror. The research was conducted in Class IX A. This study was an action research in the class. It was conducted in two meetings. The steps of the research were survey, planning, action and observation, and reflection. The subjects of the research were 17 students of IX A class. The data collected were in the form of qualitative data. The qualitative data were gained from observation. The result of the research showed that the Comic Strips can use to teach narrative reading comprehension. In order to be successful in teaching reading a narrative text to junior high school students, teacher is suggested to be able to create an interesting and effective way. In writing this paper, the researcher expects the teacher to motivate the students in reading process by using comic strips in MTs Al-Abror. It is suggestions to the teacher to use this media for the students to initiate them to read more in this fun way.